On a functional equation related to a generalization of Flett's mean value theorem - T. Riedel; Maciej Sablik (International Journal of Mathematics and Mathematical Sciences)
In this paper, we characterize all the functions that attain their Flett mean value at a particular point between the endpoints of the interval under consideration. These functions turn out to be cubic polynomials and thus, we also characterize these.